2007
DOI: 10.1097/gim.0b013e31804ec075
|View full text |Cite|
|
Sign up to set email alerts
|

Selection of family members for communication of cancer risk and barriers to this communication before and after genetic cancer risk assessment

Abstract: Purpose: The impact of genetic cancer risk assessment on communication of cancer risk information within families is not fully known. We compared women's selection of family members for cancer risk communication and perceived barriers to this communication before genetic cancer risk assessment and 6 months afterward.Methods: Mailed surveys were used to collect prospective data from consenting women undergoing genetic cancer risk assessment because of a personal and/or family history of breast or ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
67
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 40 publications
10
67
1
1
Order By: Relevance
“…Typically In general, first degree relatives were more likely to be told of test results than more distant relatives (Blandy et al, 2003;McGivern et al, 2004;Claes et al, 2003;MacDonald et al, 2007). Distant relatives were more likely to be informed of a conclusive test result than an inconclusive result (Claes et al, 2003;Hamilton et al, 2005;Hughes et al, 2002).…”
Section: Who Are Chosen As Recipients Of Results?mentioning
confidence: 95%
See 3 more Smart Citations
“…Typically In general, first degree relatives were more likely to be told of test results than more distant relatives (Blandy et al, 2003;McGivern et al, 2004;Claes et al, 2003;MacDonald et al, 2007). Distant relatives were more likely to be informed of a conclusive test result than an inconclusive result (Claes et al, 2003;Hamilton et al, 2005;Hughes et al, 2002).…”
Section: Who Are Chosen As Recipients Of Results?mentioning
confidence: 95%
“…Many studies found that sisters were more likely to be told of test results than were brothers (Hamilton et al, 2005;McGivern et al, 2004;Claes et al, 2003;MacDonald et al, 2007). This could be because of the greater cancer risks in sisters compared to brothers in these families, especially if the teller were found to have a mutation.…”
Section: Who Are Chosen As Recipients Of Results?mentioning
confidence: 99%
See 2 more Smart Citations
“…15,17 Reasons for not communicating results to relatives include lack of a close relationship, infrequent communication, or thinking that the genetic information might upset a particular relative. [17][18][19] Despite accumulating knowledge on the psychological and communication aspects of genetic testing, little is known about the effects of the testing process on family relationships per se. Although positive family relationship effects have been reported more frequently than negative ones, these results come mainly from cross-sectional studies with small samples and with a time since result disclosure, which varied considerably between subjects.…”
Section: Introductionmentioning
confidence: 99%